High Index Values of Enzyme-Linked Immunosorbent Assay for BP180 at Baseline Predict Relapse in Patients With Bullous Pemphigoid - Koga, Hiroshi; Teye, Kwesi; Ishii, Norito; Ohata, Chika; Nakama, Takekuni (Frontiers in Medicine, 2018)
Bullous pemphigoid (BP) presenting with erythema plaques and tense blisters is the most frequent autoimmune bullous disease. Immunologically, BP is characterized by the presence of circulating anti-epidermal basement membrane zone (BMZ) antibodies. The autoantigens in BMZs targeted by patient's antibodies are mainly BP180 (type XVII collagen) and BP230. Previous reports have indicated that IgG to the immunodominant region of BP180 in BP, 16th non-collagenous domain (NC16A), and anti-BP180NC16A IgE are related to disease activity. In the cytokine profile, serum levels of IL-6, TNF-α, IL-15, and CCL18 were associated with the severity or activity of the disease. Blood eosinophilia is seen frequently, especially in severe cases. These biomarkers are helpful to evaluate efficacy of treatment and disease severity. Due to the high frequency of disease relapse, prediction of relapse at initiation of treatment (baseline) must be beneficial for clinicians. Therefore, we evaluated biomarkers anti-BP180 IgG (BP180 ELISA), anti-BP230 IgG (BP230 ELISA), peripheral eosinophils, and serum IgE at baseline between BP patients with (n = 16) and without (n = 31) relapse. We found significantly higher index values of BP180 ELISA in the relapse group, whereas no significant difference was found in BP230 ELISA, peripheral eosinophils, and serum IgE. This study indicated that a high index value of BP180 ELISA (cutoff value, 53.09 U/mL; sensitivity, 81.3%; specificity, 48.4%) at baseline may predict relapse in patients with BP. This may help clinicians treating BP patients in decision-making regarding duration and intensity of treatment.